2012
DOI: 10.1080/13575279.2012.713853
|View full text |Cite
|
Sign up to set email alerts
|

The “Key” to Successful Transitions for Young People Leaving Residential Child Care: The Role of the Keyworker

Abstract: In the absence of mandatory planning and support to assist all young people who leave care in Ireland, after-care provision is a ''neglected'' area of service provision and has been criticised for being inconsistent and ad hoc. The benefits of keyworker support for young people making the transition out of care is more clearly articulated within the literature and across policy statements and is firmly embedded as a model of good practice in working with young people in residential care. The study reported her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
0
24
0
1
Order By: Relevance
“…Estas propostas partiram do pressuposto de que a transição para a vida adulta está infl uenciada por uma série de fatores que extrapolam a responsabilidade individual, para intervir terapeuticamente na expressão de emoções associadas à saída do acolhimento e na construção de relacionamentos saudáveis (Goyette et al, 2016). Por outro lado, propostas como The Outreach (Greeson et al, 2014) e Keyworking (Holt & Kirwan, 2012) apostaram no sistema de mentoria para desenvolver a rede de apoio social ao mesmo tempo em que ofereceram treinamento de habilidades. O relacionamento com mentores vem sendo apontado como uma estratégia efetiva para promover resiliência e amenizar o caminho normalmente árduo que enfrentam os jovens com história de acolhimento (Greeson, 2013).…”
Section: Discussionunclassified
“…Estas propostas partiram do pressuposto de que a transição para a vida adulta está infl uenciada por uma série de fatores que extrapolam a responsabilidade individual, para intervir terapeuticamente na expressão de emoções associadas à saída do acolhimento e na construção de relacionamentos saudáveis (Goyette et al, 2016). Por outro lado, propostas como The Outreach (Greeson et al, 2014) e Keyworking (Holt & Kirwan, 2012) apostaram no sistema de mentoria para desenvolver a rede de apoio social ao mesmo tempo em que ofereceram treinamento de habilidades. O relacionamento com mentores vem sendo apontado como uma estratégia efetiva para promover resiliência e amenizar o caminho normalmente árduo que enfrentam os jovens com história de acolhimento (Greeson, 2013).…”
Section: Discussionunclassified
“…As stated earlier, this article reports on a project initiated in 2011 (Holt & Kirwan, 2012) concerned with exploring key working and relationship-based approaches in residential child care practice, from the perspectives of residential social care workers and young care leavers. The first phase of this study accessed participants through the National Residential Child Care Managers Forum, the National AfterCare Workers Forum and a third national organisation, which advocates on behalf of young people either living within or graduated from the Irish care system.…”
Section: Methodsmentioning
confidence: 99%
“…The role of the key worker in fostering this felt security through the medium of relationship-based practice is, therefore, an obvious consideration. However, to date, there has been a dearth of research with young care leavers regarding their views on the relationship-based approach to working with children in care and the role of the key worker (Holt & Kirwan, 2012). However, it has been acknowledged in more general terms that 'the downplaying of relationship has led to serious gaps in practice' (Turney, 2012, p. 150).…”
Section: The Value Of a Secure Base In Cared-for Relationshipsmentioning
confidence: 99%
See 1 more Smart Citation
“…On another note, child care workers are the most influential part of a child's life, as they are the ones who interact with the child on a daily basis (Silva et al 2014). While in some contexts it has been found that such workers perfectly understood their roles and responsibilities, emphasized building a long-lasting relationship with children, and acknowledged that children need to feel a sense of love and belonging (Holt and Kirwan 2012), more studies have found that child care workers in residential care have a low educational level and limited experience (Ainsworth and Thoburn 2014). Moreover, Siyavora (2010) discovered in a questionnaire presented to childcare workers about their previous experience dealing with orphaned children that only one respondent out of 20 had previous experience of working with orphaned children.…”
Section: Opportunities Threatsmentioning
confidence: 99%